Respostas

2012-12-08T15:21:41-02:00

Lá vai. É só considera assim .

 

x^{2} = y \\ \\ Entao: y^{2} - 3y -40 = 0 \\ y = 3 +- \sqrt{-3^2-4*1*(-40)} / 2 * 1 \\ y = 3 +- \sqrt{9 + 169} / 2 \\ y = 3 +- 13 / 2 \\ y' = 16/2 = 8  \\ y'' = -10 / 2 = -5 \\ Como \ a \ solucao\ nao \ admite\ numero\ negativo\ entao \temo \8 \como\ raiz \\ \\ Como \ x^2 = y \ e \ y = 8 \\ x = +- \sqrt{8} \\ \\ como \8 \nao\ tem \raiz \exata\ portanto \ devemos \ fatora-lo \\ 8|2 \\ 4|2\\ 2|2\\ 1\\ Teremos \ entao : \\ \\ x =+- \sqrt{2^2*2}